CORRELATIONS BETWEEN IMMUNAL AND INNER ORGANS OF RATS AFTER THE INFLUENCE OF ELECTROMAGNETIC FIELD AND INJECTIONS OF ECHINACEA PURPUREA SOLUTION [translations pending] - Sharapova, E.N. (Світ медицини та біології, 2013)
In the following investigation correlations between morphological indexes of the immune system’s organs and reproductive system’s organs of the rots are presented. Correlations appeared after radiation of the rats with high voltage low frequency electromagnetic field. After that, for preventing degenerative changes in the organs, rats have received the Echinacea purpurea solution.